Use of Selected Periphyton Species to Improve the Water Quality and Shrimp Postlarval Production - Khatoon, Helena (2006)
In marine shrimp larval rearing practices, a large amount of water has to be exchanged frequently in order to maintain good water quality. This procedure contributes to the eutrophication of aquatic environment due to flushing of nutrient-enriched waters from aquaculture facilities. Furthermore, the process of frequent water exchange will eventually result in lack of good water supply which can also increase the risk of diseases in the hatchery. To overcome eutrophication and the risk of diseases, an alternative eco-friendly method was investigated to decrease harmful compounds especially ammonia and nitrite by using periphyton grown on substrates. Different periphyton species (Oscillatoria, Navicula sp., Cymbella sp. and Amphora sp.) from marine shrimp culture ponds were isolated, purified and mass cultured in the laboratory and grown in Conway medium. The effects of salinity (0, 15, 20, 25, 30 and 35 ppt) on the growth of these genera under aboratory condition was determined. The highest (p<0.05) growth was achieved at 25-35 ppt salinity. Nutritional composition of different periphyton genera were analysed to determine their importance as shrimp feed. All periphyton genera contained high protein (Oscillatoria 42%, Cymbella 43%, Navicula 49% and Amphora 44% of dry wt.), lipid (Oscillatoria 20%, Cymbella 26%, Navicula 26% and Amphora 23% of dry wt.) and carbohydrates (Oscillatoria 24%, Cymbella 20%, Navicula 11% and Amphora 18% of dry wt.). The periphyton genera also contained of docosahexaenoic acid (DHA) (Navicula 2%, Cymbella 2%, and Amphora 3%, Oscillatoria 1% of total lipid) and ecosapentaenoic acid (EPA) (Amphora 15%, Cymbella 3%, Navicula 8% and Oscillatoria 1% of total lipid). Periphyton colonization using different substrates (bamboo, polyvinylchloride pipe, plastic sheet, fibrous scrubber and ceramic tile) in intensive shrimp culture ponds were studied for a period of 60 days. Nineteen periphyton genera dominated by the Chlorophyceae colonized the substrates during the first 15 days. Periphyton colonization on bamboo showed the highest biomass (p<0.05) amongst all the substrates used. Biomass of periphyton in terms of chlorophyll-a varied from 179 to 1137 μg m-2 with mean values of 1137 ± 0.6, 929 ± 0.6, 684 ± 1.2, 179 ± 0.6 and 658 ± 0.6 μg m-2 on bamboo, polyvinyl chloride (PVC) pipe, plastic sheet, fibrous scrubber and ceramic tile respectively on first 15 days. Effectiveness of different periphyton genera in reducing total ammonia nitrogen (TAN), nitrite nitrogen (NO2–N) and soluble reactive phosphorous (SRP) in hatchery tanks without shrimp postlarvae were studied for a period of 16 days. It was found that Oscillatoria significantly reduced (p<0.05) TAN (90%), SRP (83%) and NO2–N (91%) whereas diatom species decreased 60%, 74% and 78% of the same parameters respectively. In addition, Oscillatoria yielded the highest (p<0.05) biomass compared to other periphyton species. Results of this study showed that all the periphyton genera were able to significantly reduce TAN, SRP and NO2-N concentrations in larval rearing tanks. The use of periphyton coated substrate (periphyton grown on polyvinylchloride pipes) for improving water quality and survival of shrimp postlarvae in hatchery without water exchange was studied for a period of 16 days. Periphyton species significantly reduced (p<0.05) TAN in shrimp culture tanks as compared to the control (without periphyton coated substrate). Amongst the treatments, tanks with Oscillatoria had the lowest mean TAN (0.09 ± 0.00 mg L-1) compared to tanks with diatoms (3.77 ± 0.17 mg L-1) and the control (5.17 ± 0.08 mg L-1). Similarly, NO2–N (0.04 ± 0.00 mg L-1) and SRP (0.22 ± 0.00 mg L-1) concentrations were significantly (p<0.05) lower in the shrimp culture tanks with periphyton species than the control (4.13 ± 0.24 mg L-1). Shrimp cultured with periphyton coated substrate showed significantly higher survival (51% - 60%) than those without periphyton (37%). In addition, the shrimp postlarvae produced in this system showed high resistance to reverse salinity stress test (37% - 43%) compared to the control (26%). This study illustrated that beneficial Periphyton species could improve water quality, provide live feed and serve as refugium for the shrimp postlarvae.